Optimizing Brussels sprout (Brassica oleracea var. geminifera L.) yield through strategic sowing dates and environmental parameters across vari ous growth stages (IASH Indian Journal of Arid Horticulture, 2025)
The important exotic vegetable crop in nutritive and cultivation concern had been planted on different dates to study the environmental effect on Brussels sprout growth and yield.The experiment was conducted during 2018 and 2019 at Punjab Agricultural University, Regional Research Station, Gurdaspur. The findings revealed that yield increased significantly with rising maximum, minimum, and mean temperatures. Plant height also showed a positive response to temperature increases. Temperature exhibited a strong and significant correlation with key growth parameters such as the number of leaves, ten-fruit weight, and fruit diameter. Heat use efficiency demonstrated a positive and significant relationship with yield, plant height, number of leaves, ten-fruit weight, and fruit diameter, highlighting its relevance in predicting crop performance. The highest yield was observed when planting done on October 20, while the lowest yield was recorded for the November 10 planting. Similarly, growth attributes, including plant height, number of leaves, ten-fruit weight, and fruit diameter, improved significantly with earlier planting dates. These findings underscore the importance of optimizing planting dates and understanding environmental interactions to maximize Brussels sprout productivity and growth.